Bulk tracer diffusion in CoCrFeNi and CoCrFeMnNi high entropy alloys. (March 2018) - Vaidya, M.; Pradeep, K.G.; Murty, B.S.; Wilde, G.; Divinski, S.V.
Abstract: High entropy alloys (HEAs) have emerged as a promising class of equiatomic or near equiatomic multicomponent alloys, which garner fundamental curiosities and interest in high temperature applications. Understanding diffusion kinetics of HEAs is critical to assess their phase stability and deformation behaviour, particularly at elevated temperatures. For the first time, bulk tracer diffusion coefficients of Co, Cr, Fe and Mn are determined in polycrystalline CoCrFeNi and CoCrFeMnNi HEAs using the radiotracer method in the temperature interval of 1073–1373 K. Material homogeneity and the absence of any phase decomposition in CoCrFeNi and CoCrFeMnNi HEAs were established by electron microscopy and atom probe tomography investigations. Both bulk and grain boundary diffusion contributions to penetration profiles are observed for diffusion of Co, Cr, Fe and Mn tracers in both HEAs. The temperature dependencies of bulk diffusion for all tracers show Arrhenius behaviour. The corresponding activation energies ( Q ) and the logarithm of pre-exponential factors ( D 0 ) show a linear relationship, thus following the "compensation rule". An increase of the configurational entropy leads to reduced diffusion rates only when a homologous temperature scale is used for comparison. The increase of activation energy barrier and lower frequency factors both contribute to the decreased diffusion rates. A cross-over temperature (Tc = 1020 K) is observed for Co diffusion (on slight extrapolation of Arrhenius plot) in CoCrFeNi and CoCrFeMnNi HEAs, while Cr and Fe exhibit almost parallel Arrhenius lines. Above Tc, the Co diffusivity is higher in CoCrFeMnNi than in CoCrFeNi, which suggests that diffusion in HEAs need not be assumed to retard with an increasing number of elements. The existence of a cross-over temperature correlates with the change in binding energy (or enthalpy) of the constituents from CoCrFeNi to CoCrFeMnNi. Graphical abstract: Image 1